2023
DOI: 10.1080/21645515.2023.2188856
|View full text |Cite
|
Sign up to set email alerts
|

Bivalent second booster dose of the COVID-19 vaccine: Eligible populations’ reasons for receiving in Italy

Abstract: The Italian Ministry of Health recommended the administration of the bivalent second booster dose of the new available mRNA COVID-19 vaccine for subjects aged 60 y and over, aged 12 y and over with high frailty motivated by concomitant/preexisting conditions, and health-care workers. The purposes of this cross-sectional survey were to investigate the reasons for receiving the bivalent second booster dose of the COVID-19 vaccine and associated influencing factors among the eligible population attending two immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 50 publications
(24 reference statements)
3
6
0
Order By: Relevance
“…Our systematic review shows no safety concerns in BV booster recipients and is consistent with the observational cohort study in children and adolescents [50,51]. Furthermore, multiple reasons for not receiving a BV have been identified, including a lack of awareness of eligibility for vaccination, vaccine availability, and perceived immunity against infection [52,53]. Our study demonstrates the equal immunogenicity of the BV to the MV without safety concerns.…”
Section: Discussionsupporting
confidence: 85%
“…Our systematic review shows no safety concerns in BV booster recipients and is consistent with the observational cohort study in children and adolescents [50,51]. Furthermore, multiple reasons for not receiving a BV have been identified, including a lack of awareness of eligibility for vaccination, vaccine availability, and perceived immunity against infection [52,53]. Our study demonstrates the equal immunogenicity of the BV to the MV without safety concerns.…”
Section: Discussionsupporting
confidence: 85%
“…The survey showed that the participants had received vaccination-related information from HCWs, also in combination with a variety of other sources, as the most used source. This result corresponds to findings obtained in other similar surveys conducted in this and in other geographic areas [ 28 , 39 , 40 , 41 , 42 ]. Moreover, the results of the multinomial and multivariate logistic regression analysis demonstrated that HCWs were the most important communication source in disseminating accurate information about vaccinations aimed at mitigating the risk and other public health threats.…”
Section: Discussionsupporting
confidence: 92%
“…Data for this cross-sectional survey were part of a broader project seeking to evaluate perceptions and behaviors toward COVID-19 vaccination in different groups in southern Italy ( 12 19 ). Data collection took place from January to March 2023 in seven public kindergartens and eight public nursery schools randomly selected in the geographic area of Naples, the southern part of Italy.…”
Section: Methodsmentioning
confidence: 99%